Simulasi Pencarian Rute Terpendek Bagi Pengguna Transportasi Bus Trans Jakarta Indonesia - Pasaribu, Novie Theresia Br.; -, Ratnadewi (Zenit, 2012)
Traffic jams occur in the capital city of Jakarta. The price increase of  fuel, daily tasks/activities demand that everyone have fast journey with economical cost, and save energy. The Jakartaâs residents then make use of Trans Jakarta Bus Indonesia (Bus Way) facility as one solution to get  faster transportation, comfortable seats, and economical cost. This research proposes  the design and simulation realization of searching the shortest route for the Trans Jakarta Bus Indonesia by using a combination of Iterative Deepening (ID) and Djikstra Algorithm. It is expected that the busway commuters can choose  the right route to reach their destination with cost-effective travels. ID Algorithm is a searching algorithm  which expands all possible routes from the initial to the final state. Djikstra Algorithm is a searching algorithm of the solution value that considers distance depending on the smallest cost (the shortest path). The shortest route searching simulation using the combination of ID and Djikstra Algorithm has successfully been recognized. By using 12 testing samples of the various traveling cases, the researchens notice the average processing  time of this application, namely 0.733 second. The simulation program gives the information of the shortest route, most efficient cost, and best public facilities for the bus way commuters.  Keywords: Simulation, the shortest route, Iterative Deepening Algorithm, Djikstra Algorithm.